Deformation forecasting and stability analysis of large-scale underground powerhouse caverns from microseismic monitoring. (July 2016) - Dai, Feng; Li, Biao; Xu, Nuwen; Fan, Yilin; Zhang, Chuanqing
Abstract: To assess the stability of the underground powerhouse caverns and analyse the failure mechanism of the surrounding rock mass at the Baihetan hydropower station in southwest China, a high-resolution microseismic (MS) monitoring system was implemented in the left-bank underground powerhouse caverns. Based on the temporal and spatial distribution of MS events, the correlation between MS activities and construction was established, and three damage regions for the surrounding rock mass during excavation were identified. MS clusters were found to occur most often in stress-concentration regions of the underground powerhouse caverns and to result from various factors, including excavation-induced unloading and geological structure activation. The seismic source parameters (i.e., moment magnitudes and (S-wave) to (P-wave) energy ratios, E s / E p ) of the three MS clusters demonstrate the different failure modes and risks of the surrounding rock mass. The temporospatial evolution of the MS activities, apparent stress, and cumulative apparent volume in localized rock mass during the period of a typical large deformation were used to develop a comprehensive analytical method for forecasting the deformation of the surrounding rock mass. Thus, this comprehensive analytical method, which incorporates MS monitoring, conventional monitoring, geological survey and construction, is promising for identifying the damage zones and forecasting the macro-deformation of the surrounding rock mass in underground powerhouse caverns subjected to excavation. Highlights: MS monitoring and evaluate stability of underground caverns subject to excavation. Temporospatial distribution characteristics of microseismicity are analysed. Different formation mechanisms of MS event clusters are revealed. Different MS parameters are used to demonstrate failure modes of rock mass. Propose a comprehensive method to forecast rock mass deformation.